2015
DOI: 10.4238/2015.may.18.8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of changes in serum endostatin and fibroblast growth factor 19 on the chemotherapeutic sensitivity in acute myeloid leukemia patients

Abstract: ABSTRACT. The present study aimed to explore the changes in serum endostatin and fibroblast growth factor 19 (FGF-19) in acute myeloid leukemia patients, and to determine their effects on chemotherapeutic sensitivity. Sixty acute myeloid leukemia patients and 30 healthy controls were included in the study. Patient serum endostatin and FGF-19 levels were measured on admission, and then, standard chemotherapy was administered. The patients were divided into 2 groups according to chemotherapeutic effects: 21 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…FGFR are required for the biological activities of FGF; the activated FGFR phosphorylate specific tyrosine residues that mediate interaction with the JAK/STAT, PI3K-AKT, and RAS-MAPK pathways [44]. Su et al [45] observed that the levels of FGF-19 in AML patients before chemotherapy were significantly higher than those in a control group. Although FGF19 was not among the DEGs of our global expression analysis, thus was not validated by RT-qPCR, our ARACNE results revealed that it was involved in pre-B ALL.…”
Section: Discussionmentioning
confidence: 99%
“…FGFR are required for the biological activities of FGF; the activated FGFR phosphorylate specific tyrosine residues that mediate interaction with the JAK/STAT, PI3K-AKT, and RAS-MAPK pathways [44]. Su et al [45] observed that the levels of FGF-19 in AML patients before chemotherapy were significantly higher than those in a control group. Although FGF19 was not among the DEGs of our global expression analysis, thus was not validated by RT-qPCR, our ARACNE results revealed that it was involved in pre-B ALL.…”
Section: Discussionmentioning
confidence: 99%
“…It has been confirmed that the sensitivity of serum endostatin and fibroblast growth factor 19 (FGF-19) is predicted by ROC curve analysis, thus affecting the occurrence of acute myeloid leukemia [12]. Studies have shown that the treatment of acute lymphoblastic leukemia (ALL) by bispecific T cell antigen-antibody isocitrate dehydrogenase (IDH) has made significant achievements in clinical practice [13].…”
Section: Introductionmentioning
confidence: 96%
“…It is associated with genomic alterations in cell proliferation and differentiation [ 1 , 2 ]. It has a high incidence accounts for approximately 60% of all leukemia [ 3 ]. It seriously endangers human health and life.…”
Section: Introductionmentioning
confidence: 99%
“…It seriously endangers human health and life. Chemotherapies are the main treatment for acute myeloid leukemia [ 3 , 4 ]. However, there are still poor prognosis and short disease-free survival after chemotherapy.…”
Section: Introductionmentioning
confidence: 99%